Cervical excitatory neurons sustain breathing after spinal cord injury. (18th October 2018) - Satkunendrarajah, Kajana; Karadimas, Spyridon; Laliberte, Alex; Montandon, Gaspard; Fehlings, Michael
Abstract Dysfunctional breathing is the main cause of morbidity and mortality after traumatic injury of the cervical spinal cord1, 2 and often necessitates assisted ventilation, thus stressing the need to develop strategies to restore breathing. Cervical interneurons that form synapses on phrenic motor neurons, which control the main inspiratory muscle, can modulate phrenic motor output and diaphragmatic function3–5 . Here, using a combination of pharmacogenetics and respiratory physiology assays in different models of spinal cord injury, we show that mid-cervical excitatory interneurons are essential for the maintenance of breathing in mice with non-traumatic cervical spinal cord injury, and are also crucial for promoting respiratory recovery after traumatic spinal cord injury. Although these interneurons are not necessary for breathing under normal conditions, their stimulation in non-injured animals enhances inspiratory amplitude. Immediately after spinal cord injury, pharmacogenetic stimulation of cervical excitatory interneurons restores respiratory motor function. Overall, our results demonstrate a strategy to restore breathing after central nervous system trauma by targeting a neuronal subpopulation. A population of cervical interneurons is identified that can regulate diaphragm function by modulating phrenic motor neurons; targeting this small population of neurons may be a functional strategy to restore breathing after traumatic spinal cord injury.